Postgraduate training for family medicine in a rural district hospital in South Africa: Appropriateness and sufficiency of theatre procedures as a sentinel indicator - Dawie Du Plessis; Paul Alfred Kapp; Louis S. Jenkins; Laurel Giddy (AOSIS, 2016)
Background: Since 2007, the postgraduate training of family physicians for South African district hospitals has been formalised. This training differs from European and North American programmes as up to 30% of the skills needed rely on district hospital surgical, obstetrics and anaesthetics procedures, particularly in rural areas, as outlined in the national unit standards. The aim of this study was to evaluate the appropriateness and sufficiency of learning opportunities for these skills in a rural district hospital. Methods: A descriptive, cross-sectional study was undertaken of the number and type of procedures performed in theatre for a 1-year period and compared with the required procedural skills stipulated in the national unit standards. Descriptive statistical analyses were used to analyse categorical data. Results: Three thousand seven hundred and forty-one procedures were performed during the study period. Anaesthesia was the most common procedure, followed by Caesarean section. There were adequate opportunities for teaching most core skills. Conclusions: Sufficient and appropriate learning opportunities exist for postgraduate family medicine training in all the core skills performed in a theatre according to the national unit standards. Keywords: Post Graduate Training, Family Medicine, Procedural Skills, Rural, District hospitals